Bargaining in the Presence of Condorcet Cycles: The Role of Asymmetries - Aaron Kamm; Harold Houba (Tinbergen Institute, 2015)
This paper reports results from a laboratory experiment studying the role of asymmetries, both in payoffs and recognition probabilities, in a model of strategic bargaining with Condorcet cycles. Overall, we find only limited support for the equilibrium predictions. The main deviations from theory are: a) Subjects under-exploit their bargaining power by being more accommodating in their acceptance decision than predicted; b) subjects change in behavior in reaction to asymmetric recognition probabilities exhibits systematic deviations from theory. This suggests that subjects do not fully grasp the subtle effects asymmetries have on bargaining power, especially when the asymmetries relate to recognition probabilities.
Keywords: C73; C78; C91; C92; D72; 330; Bargaining; Condorcet Paradox; Experiments; Voting; Committees